SISTEM INFORMASI POINT OF SALE BERBASIS WEB PADA DISTRIBUTOR ALAT KESEHATAN - Efrans Christian; Widiatry Widiatry (Universitas Palangka Raya, 2023)
PT. Riyani Jaya Mandiri is a distributor company engaged in the sale of medical devices, in the Central Kalimantan area, this company itself often has difficulty in managing sales transaction data because the existing information system often experiences problems and does not work well, so that some process back using manual or conventional methods. Based on these problems, a Point of Sales (POS) application was developed which aims to build a system that can process sales transaction data computerized and integrated with the database so that the management, search, and reporting of transaction data becomes faster. . In its manufacture, the Waterfall Methodology is used. The result of this research is a web-based Point of Sales (POS) application that was built to adapt the existing business processes at PT. Riyani Jaya Mandiri which can manage product data, customer data and transaction data so that it can provide information on sales activities to the company in order to take decisions and actions in improving service quality and sales to customers.